Development of an Empirical Coefficient for the Short Circuit Current to Determine Soiling Effect on PV Performance (University of Khartoum Engineering Journal, 2022)
In this study, the effect of dust accumulation on the performance of photovoltaic (PV) module has been shown. A statistical analysis has been conducted on a medium sized sample data collected from 30 hours of experimental work to obtain an empirical coefficient like temperature coefficients of short circuit current and open circuit voltage usually provided by manufacturers. This coefficient will be named dust coefficient of short circuit current and it will represent a predefined range of environmental conditions and soiling amounts; as the available testing conditions, and the statistical model prediction limits bound the coefficient extent of applicability.
Keywords: Solar energy; Photovoltaic; Soiling; Statistical modelling.